Analisis Perbandingan Produksi Cabai di Kabupaten Ciamis - Subagja, Syukur; Wulandari, Eliana; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Ciamis Regency is one of the main areas for horticultural agriculture in West Java for chili commodities, where there are five sub-districts as the main contributors to chili production, including Sukamantri, Panumbangan, Panjalu, Cihaurbeuti and Panawangan sub-districts. The aim of this research is to see whether there are significant differences in chili production and evaluate the production levels of the five sub-districts in Ciamis Regency during the period 2018 to 2022. The data collection method uses library research using secondary data taken from BPS Ciamis Regency. One Way ANOVA test was carried out to test the proposed hypothesis. The results of the research show that there are significant differences in chili production between Sukamantri sub-district and four other sub-districts, namely Panjalu, Panumbangan, Cihaurbeuti and Panawangan sub-districts. However, there are no significant differences between the four sub-districts, so it is assumed that the average production output is almost the same.